Development of osteological structures in the sea bream Vertebral column and caudal fin complex - Faustino, M. (2014)
The development of cartilaginous structures in cultured sea bream Sparus aurata larvae and the timing of their ossification was studied. In cultivated sea bream larvae the first cartilaginous structure to be identified was hypural 1 at 4·1 mm notochord length (LN). By 5·3 mm LN, prior to the onset of ossification, it was possible to distinguish the following cartilaginous structures: all 23 neural arches, all 13 haemal arches and two of the four pairs of parapophyses. The neural arches 1–4 and 15–23 were formed on the notochord and elongated dorsally, while neural arches 5–14 appeared on the dorsal side of the spinal cord and elongated ventrally. Initiation of ossification occurred at 5·7–6·0 mm standard length (LS) when the cartilaginous ontogeny of the vertebral column was completed. Ossification was coincident with dorsal flexion at the posterior end of the notochord and occurred in a sequential manner: (1) dorsoanteriorly, the cartilaginous neural arches and the centra were the first structures to ossify; (2) ventrad at the centre, at 7·0–7·5 mm LS; (3) posteriorly at 7·1 mm LS the hypural complex and urostyle (24th centrum) were ossified; and (4) dorsad at the centre (neural arches and spines).